Persistent psychological distress and mortality in patients with stable coronary artery disease. Issue 23 (26th June 2017) - Stewart, Ralph A H; Colquhoun, David M; Marschner, Simone L; Kirby, Adrienne C; Simes, John; Nestel, Paul J; Glozier, Nick; O'Neil, Adrienne; Oldenburg, Brian; White, Harvey D; Tonkin, Andrew M
Abstract : Background: A single assessment of psychological distress, which includes depression and anxiety, has been associated with increased mortality in patients with coronary heart disease, but the prognostic importance of persistence of distress symptoms is less certain. Aim: To determine whether intermittent and/or persistent psychological distress is associated with long-term cardiovascular (CV) and total mortality in patients with stable coronary artery disease. Methods: 950 participants in the Long-Term Intervention with Pravastatin in Ischaemic Disease (LIPID) trial completed at least four General Health Questionnaires (GHQ-30) at baseline and after ½, 1, 2 and 4 years. In a landmark analysis from 4 years, Cox proportional hazards models evaluated the risk of CV and total mortality by increasing levels of psychological distress: never distressed, sometimes any severity (GHQ score >5), persistent mild (GHQ score >5 on three or more occasions) and persistent moderate distress (GHQ score >10) on three or more occasions, over a median of 12.1 (IQR 8.6–12.5) years. The models were both unadjusted and adjusted for known baseline risk factors. Results: Persistent moderate or greater psychological stress was reported on three or more assessments by 35 (3.7%) subjects. These patients had a higher risk of both CV death (adjusted HR 3.94, 95% CI 2.05 to 7.56, p<0.001) and all-cause mortality (adjusted HR 2.85, 95% CI 1.74 to 4.66, p<0.001) compared with patients with no distress. In contrast, patients who reported persistent mild distress (n=73, 7.7%) on three or more visits, and those who met criteria for distress on only one or two assessments (n=255, 26.8%), did not have an increased risk of CV or all-cause mortality during follow-up. Conclusion: In patients with stable coronary artery disease, persistent psychological distress of at least moderate severity is associated with a substantial increase in CV and all-cause mortality.